Mesenchymal stem cells attenuate adriamycin‐induced nephropathy by diminishing oxidative stress and inflammation via downregulation of the NF‐kB. Issue 5 (25th April 2018) - Song, In‐Hwan; Jung, Kyong‐Jin; Lee, Tae‐Jin; Kim, Joo‐Young; Sung, Eon‐Gi; Bae, Young Chul; Park, Yong Hoon
Abstract: Aim: This study aimed to evaluate the molecular mechanism mitigating progress of chronic nephropathy by mesenchymal stem cells (MSCs). Methods: Rats were divided into normal control (Normal), adriamycin (ADR)+vehicle (CON), and ADR+MSC (MSC) groups. Nephropathy was induced by ADR (4 mg/kg) and MSCs (2 × 10 6 ) were injected. Rats were euthanized 1 or 6 weeks after ADR injection. NF‐kB, MAPKs, inflammation, oxidative stress, profibrotic molecules, and nephrin expression were evaluated. Electron and light microscopy were used for structural analysis. MSCs were co‐cultured with renal tubular epithelial cells or splenocytes to evaluate relation with oxidative stress and inflammatory molecules Results: Adriamycin treatment upregulated inflammation, oxidative stress, and profibrotic molecules; this was mitigated by MSCs. Glomerulosclerosis and interstitial fibrosis were observed in ADR‐treated groups, and were more prominent in the CON group than in the MSC group. Fusion of foot processes and loss of slit diaphragms were also more prominent in the CON group than in the MSC group. In vitro, MSCs reduced oxidative stress related molecules, inflammatory cytokines, and NF‐kB transcription. MSC‐ or ADR‐induced regulation of NF‐kB transcriptional activity was confirmed by a luciferase reporter assay. Conclusions: Mesenchymal stem cells attenuate ADR‐induced nephropathy by diminishing oxidative stress and inflammation via downregulation of NF‐kB. Summary at a Glance: This study reports the protective effect of mesenchymal stem cells (MSC) in an adriamycin‐induced inflammatory model of acute kidney injury that leads to glomeruosclerosis. Using in vitro and in vivo assays, the NK‐kappa beta signaling pathway was determined to be a major pathway for oxidative stress as a result of injury that is reduced following MSC therapy.